Quality of life nurses on covid-19 pandemic with curhat online - Vianti, Remilda Armika; Hasanah, Nunung (MEDIA ILMU KESEHATAN, 2021)
Background: Nowadays people are prefer to used social media to explore their feeling, 90 % Indonesian people using social media like facebook, instragram and whatups. Their feeling comfort during expessing by social media. Covid 19 nurses experienced discriminasing and stigma in community. Therefor their using social media to explaine their emotional feeling. Culun is media for Nurses who carring covid 19 patient to expressing their anciety and fear and quality of life is survival indicator when their accepted the codition.Objective: To described the effect of Culun (group discussion) for Quallity of Life Nurses on Covid-19 PandemicMethod: The method in this research is a quasi experiment with one group pre and post design. 26 respondents were included in the discussion group (CULUN) and then measured the Quality of Life using the (WHOQOL) -BREF instrument. Subject in this reasearc is nurses who caring covid 19 patient in hospital around Pekalongan city. The data was analized by paired sample T-Test.Result: The result for this study is there are effect of culun for quallity of life nuses who taking care of covid 19 patient.Conclusion: We interveneby creating online groups for discussion using whats app. We sent instrument for pretest before discussion and post test after discussion via whats app groups. Appraisal for this research is increasing for quality of life. There is effect of culun of quality of life nurses on covid 19 pandemic.